2019
DOI: 10.1007/s12541-019-00255-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of Soft Actuator Materials

Abstract: Soft actuator materials change their shape or size in response to stimuli like electricity, heat, light, chemical or pH. These actuator materials are compliant and well suited for soft mechatronics and robots. This paper introduces the definition of soft materials and the position of soft actuator materials in comparison with conventional actuators and other solid state actuator materials. A thorough review of selected soft actuator materials is carried out, including responsive gels/hydrogels, ionic polymer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 145 publications
0
108
0
Order By: Relevance
“…At a time when the expansion of artificial systems through our society is rapidly blooming, the research on soft actuators becomes more and more appealing and necessary. [ 1,2 ] Liquid crystal elastomers (LCEs), as a type of stimuli‐responsive materials, [ 3–7 ] exhibit outstanding reversible shape‐memory properties when exposed to external stimulations. [ 8–13 ] Since De Gennes [ 14 ] predicted the possibility of making LCE actuators in 1975, the continuous research and developments on LCEs attracted considerable attention and found potential applications as artificial muscles, [ 15–17 ] smart sensors, [ 18–20 ] motors, [ 21 ] and actuators.…”
Section: Methodsmentioning
confidence: 99%
“…At a time when the expansion of artificial systems through our society is rapidly blooming, the research on soft actuators becomes more and more appealing and necessary. [ 1,2 ] Liquid crystal elastomers (LCEs), as a type of stimuli‐responsive materials, [ 3–7 ] exhibit outstanding reversible shape‐memory properties when exposed to external stimulations. [ 8–13 ] Since De Gennes [ 14 ] predicted the possibility of making LCE actuators in 1975, the continuous research and developments on LCEs attracted considerable attention and found potential applications as artificial muscles, [ 15–17 ] smart sensors, [ 18–20 ] motors, [ 21 ] and actuators.…”
Section: Methodsmentioning
confidence: 99%
“…[48] Although several active materials have been developed for use in soft actuators, only a few exhibit characteristics that make them suitable for use in bio-inspired, untethered, infrareddriven, reversible, and reprogrammable soft actuators. [45,49] In this article, we propose a method for the fabrication of an infrared-driven, untethered, reversible, and reprogrammable actuator for soft bio-inspired robots. A polymer bilayer structure comprising an infrared response layer (IR-layer) and a transparent elastic layer (T-layer) was fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electricity-triggered changes in polymer materials present some progress, with the most notable examples dealing with dielectric soft actuators employing ultrahigh electric fields or electro-strictive elastomers. 28,29,30,31,32 However, electricity-induced changes in material properties, even simple on/off softening effects, are unprecedented in highly-reinforced high-performance bioinspired nanocomposites.…”
Section: Introductionmentioning
confidence: 99%